Pedagogical planning: Construction of traditional and constructive classes (Research, Society and Development, 2023)
In the current educational panorama, it is seen that the need for a lesson plan based on the student's needs still faces problems in its production. The current study presents reflections on the pedagogical planning of teachers at a high school in Maracanaú – Ceará - Brazil, enabling a broader understanding of this activity, its objectives, its forms of execution, its approaches and its evaluation possibilities. Thus, aiming to reaffirm the importance of planning, as a tool used by the teacher, to carry out classes that contribute to the cognitive development of students in the teaching-learning process. We analyzed ten lesson plans, from different areas of knowledge, based on what was proposed by several authors. After obtaining authorization from the authors of the plans, we collected ten samples, from annual plans, and one from a weekly plan, with the coordination of the aforementioned school. We then proceeded to study them in the light of the aforementioned theoretical assumptions. It was found that when executing a plan, the teacher organizes his work, systematizes his actions, increases teacher productivity and avoids improvisations that do not contribute to the development of students. We point out that the plans analyzed excel in specifying the content and activities that must be done in the classroom. However, some of them lacked reflection on the contents applied and developed in the classroom, throughout the course. The evaluated weekly planning showed greater concern in specifying the procedures and stages of student assessment, pointing to its constructivist core of its production.